Implementation of Self-Hosted IoT Ecosystem on NPK Soil Monitoring System - Nugroho, Aditya Bakti; Hasibuan, Faisal Candrasyah; Perdana, Doan (Universitas Telkom, 2025)
In previous research, a tool has been made to detect soil NPK nutrient content with a screen display on the device. However, the reading results of the system cannot be monitored remotely. This research aims to develop a self-built IoT ecosystem to monitor the readings remotely. On the device side, a microcontroller can connect to the internet via a Wi-Fi network. The communication protocol selected is the MQTT protocol based on the pub-sub model. The software chosen to present the data is Node-RED. The service is self-hosted using a personal computer (PC). To be accessed from the internet, a tunneling service is used. The data presentation service obtained can be accessed remotely. Based on the test results, the MQTT protocol allows sending data only in the size of tens of bytes with an average delivery time of under one second. The data is presented in a dashboard that can be accessed via the internet with a browser.